Group Classification of a General Bond-Option Pricing Equation of Mathematical Finance - Tanki Motsepa; Chaudry Masood Khalique; Motlatsi Molati (Abstract and Applied Analysis)
We carry out group classification of a general bond-option pricing equation. We show that the equation admits a three-dimensional equivalence Lie algebra. We also show that some of the values of the constants which result from group classification give us well-known models in mathematics of finance such as Black-Scholes, Vasicek, and Cox-Ingersoll-Ross. For all such values of these arbitrary constants we obtain Lie point symmetries. Symmetry reductions are then obtained and group invariant solutions are constructed for some cases.